‘Cerejeira da mata’ and ‘guabijuzeiro’ propagation by air layering - Hossel, Cristiano; Wagner Júnior, Américo; Hossel, Jéssica Scalet Alves de Oliveira; Fabiane, Keli Cristina; Citadin, Idemir (Comunicata Scientiae, 2018)
‘Guabijuzeiro’ and ‘cerejeira da mata’ are plant species from the Myrtaceae family, with many difficulties in asexual multiplication. Thus, the aim of this study was to evaluate ‘cerejeira da mata’ (Eugenia involucrata DC.) tree and ‘guabijuzeiro’ [Myrcianthes pungens (Berg) Legrand] tree propagation by air layering, using different IBA concentrations (0, 1000 , 2000 and 3000 mg L-1) and materials to wrap the substrate (transparent plastic, black plastic and transparent plastic + aluminum foil). The experimental design for both experiments was a randomized blocks, in a 3 x 4 factorial (wrapping material x IBA concentration), with three repetitions of five air layering each. After 180 days, the percentage of rooting, length and number of roots were evaluated. Sixty days after rooting the percentage of survival plants were evaluated. The air layering technique was not efficient in the ‘guabijuzeiro’ propagation. This technique could be used in ‘cerejeira da mata’ plants without the IBA application and using transparent plastic, but with low performance.